(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
The human heart functions as a highly efficient biomechanical pump, governed by fundamental physical principles such as pressure gradients, fluid dynamics, and mechanical force generation. This article explores the biomechanical and physical properties underlying cardiac activity, focusing on the interaction between myocardial contraction, blood flow, and vascular resistance. Special attention is given to the role of hemodynamic parameters, including cardiac output, stroke volume, and arterial pressure, in maintaining systemic circulation. The study also highlights how alterations in these physical mechanisms can contribute to pathological conditions. Understanding the physical basis of cardiac function provides valuable insights for both clinical practice and biomedical research.